Measuring client satisfaction and the quality of family planning services: A comparative analysis of public and private health facilities in Tanzania, Kenya and Ghana - Agha Sohail; Do Mai; Hutchinson Paul L (BMC, 2011)
Abstract Background Public and private family planning providers face different incentive structures, which may affect overall quality and ultimately the acceptability of family planning for their intended clients. This analysis seeks to quantify differences in the quality of family planning (FP) services at public and private providers in three representative sub-Saharan African countries (Tanzania, Kenya and Ghana), to assess how these quality differentials impact upon FP clients' satisfaction, and to suggest how quality improvements can improve contraceptive continuation rates. Methods Indices of technical, structural and process measures of quality are constructed from Service Provision Assessments (SPAs) conducted in Tanzania (2006), Kenya (2004) and Ghana (2002) using direct observation of facility attributes and client-provider interactions. Marginal effects from multivariate regressions controlling for client characteristics and the multi-stage cluster sample design assess the relative importance of different measures of structural and process quality at public and private facilities on client satisfaction. Results Private health facilities appear to be of higher (interpersonal) process quality than public facilities but not necessarily higher technical quality in the three countries, though these differentials are considerably larger at lower level facilities (clinics, health centers, dispensaries) than at hospitals. Family planning client satisfaction, however, appears considerably higher at private facilities - both hospitals and clinics - most likely attributable to both process and structural factors such as shorter waiting times and fewer stockouts of methods and supplies. Conclusions Because the public sector represents the major source of family planning services in developing countries, governments and Ministries of Health should continue to implement and to encourage incentives, perhaps performance-based, to improve quality at public sector health facilities, as well as to strengthen regulatory and monitoring structures to ensure quality at both public and private facilities. In the meantime, private providers appear to be fulfilling an important gap in the provision of FP services in these countries.